ASSESSMENT OF FLEXIBLE CARBON CAPTURE AND UTILIZATION OPTIONS APPLIED TO GASIFICATION PLANTS - PETRESCU, Letitia; DINCĂ, Cristian; CORMOS, Călin-Cristian (Studia Universitatis Babeș-Bolyai Chemia, 2020)
The aim of this work is to assess the energy vector poly-generation capabilities of gasification plants equipped with carbon capture and utilization (CCU) features. As evaluated energy carriers, various total or partial decarbonized vectors were investigated (e.g., power, hydrogen, synthetic natural gas, methanol, Fischer-Tropsch fuel). As illustrative examples, the gasification concepts with 100 MW net energy output were considered having an overall plant decarbonization rate of 90%. As decarbonization technologies, the gas – liquid absorption based on chemical and physical scrubbing was assessed. A broad range of process system engineering tools were used (e.g., modeling and simulation, process integration, plant flexibility elements, technical and environmental evaluation). As results show, the application of carbon capture and utilization technologies for gasification-based poly-generation has promising results in term of increasing the overall energy efficiency (up to 68%), reducing CO2 emissions (down to 7 kg/MWh) and improving cycling capabilities.